2001
DOI: 10.1046/j.1469-0705.2001.abs15-4.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the prenatal detection of structural congenital heart diseases

Abstract: Objective: To evaluate the accuracy and assess the indications of fetal echocardiography to diagnose structural heart disease in our high risk population, by an obstetric team. Methodology: Over a 4-year period, a transabdominal echocardiography was performed in 912 high risk pregnancies for congenital heart disease at 18-38 weeks of gestation. In the last 140 cases, an early examination combining either the transvaginal or the transabdominal route at 13-16 weeks was also carried out. Follow up was obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Our results may look different with a larger cohort. In 2003, Wong et al 17 reported that the experience of the sonographer did influence the detection rate of structural heart diseases. This aspect was a major strength of our study in that most the early fetal echocardiographic examinations were performed by a single sonographer with more than 25 years of experience in performing fetal echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…Our results may look different with a larger cohort. In 2003, Wong et al 17 reported that the experience of the sonographer did influence the detection rate of structural heart diseases. This aspect was a major strength of our study in that most the early fetal echocardiographic examinations were performed by a single sonographer with more than 25 years of experience in performing fetal echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…At present, approximately 50-60% of cases are detected antenatally through local and national screening programmes. [4][5][6][7] The definition of CHD varies significantly. Mitchell et al 8 define CHD as 'a gross structural abnormality of the heart or intrathoracic great vessels that is actually or possibly of functional significance'.…”
Section: Epidemiology Of Congenital Heart Defects (Chds)mentioning
confidence: 99%
“…Operator skill is the most important factor affecting the prenatal diagnosis of congenital heart disease [3,4]. Failure to diagnose a life-threatening cardiac disorder in utero may negatively impact survival because prompt postnatal intervention is required to improve outcome in fetuses with disorders such as transposition of the great arteries, hypoplastic left heart syndrome, and aortic coarctation [3,5].…”
Section: Introductionmentioning
confidence: 99%